Cementless Fixation Is Associated With Increased Risk of Early and All-Time Revision After Hemiarthroplasty But Not After THA for Femoral Neck Fracture: Results From the American Joint Replacement Registry. Issue 10 (October 2021) - Huddleston, James I.; De, Ayushmita; Jaffri, Heena; Barrington, John W.; Duwelius, Paul J.; Springer, Bryan D.
Abstract: Background: Despite ample evidence supporting cemented femoral fixation for both hemiarthroplasty and THA for surgical treatment of displaced femoral neck fractures, cementless fixation is the preferred fixation method in the United States. To our knowledge, no nationally representative registry from the United States has compared revision rates by fixation for this surgical treatment. Question/purpose: After controlling for relevant confounding variables, is femoral fixation method (cemented or cementless) in hemiarthroplasty or THA for femoral neck fracture associated with a greater risk of (1) all-cause revision or (2) revision for periprosthetic fracture? Methods: Patients with Medicare insurance who had femoral neck fractures treated with hemiarthroplasty or THA reported in the American Joint Replacement Registry database from 2012 to 2017 and Centers for Medicare and Medicaid Services claims data from 2012 to 2017 were analyzed in this retrospective, large-database study. Of the 37, 201 hemiarthroplasties, 42% (15, 748) used cemented fixation and 58% (21, 453) used cementless fixation. Of the 7732 THAs, 20% (1511) used cemented stem fixation and 80% (6221) used cementless stem fixation. For both the hemiarthroplasty and THA cohorts, most patients were women and had cementless femoral fixation. Early revision was defined as a procedure that occurred less than 90 days from the index procedure. All patients submitted to the registry were included in the analysis. Patient follow-up was limited to the study period. No patients were lost to follow-up. Due to inherent limitations with the registry, we did not compare medical complications, including deaths attributed directly to cemented fixation. A logistic regression model including the index arthroplasty, age, gender, stem fixation method, hospital size, hospital teaching affiliation, and Charlson comorbidity index score was used to determine associations between the index procedure and revision rates. Results: For the hemiarthroplasty cohort, risk factors for any revision were cementless stem fixation (odds ratio 1.42 [95% confidence interval 1.20 to 1.68]; p < 0.001), younger age (OR 0.96 [95% CI 0.95 to 0.97]; p < 0.001), and higher Charlson comorbidity index (OR 1.06 [95% CI 1.02 to 1.11]; p = 0.004). Risk factors for early revision were cementless stem fixation (OR 1.77 [95% CI 1.43 to 2.20]; p < 0.001), younger age (OR 0.98 [95% CI 0.97 to 0.99]; p < 0.001), and higher Charlson comorbidity index (OR 1.09 [95% CI 1.04 to 1.15]; p < 0.001). Risk factors for revision due to periprosthetic fracture were cementless fixation (OR 6.19 [95% CI 3.08 to 12.42]; p < 0.001) and higher Charlson comorbidity index (OR 1.16 [95% CI 1.06 to 1.28]; p = 0.002). Risk factors for early revision due to periprosthetic fracture were cementless fixation (OR 7.38 [95% CI 3.17 to 17.17]; p < 0.001), major teaching hospital (OR 2.10 [95% CI 1.08 to 4.10]; p = 0.03), and higher Charlson comorbidity index (OR 1.20 [95% CI 1.09 to 1.33]; p < 0.001). For the THA cohort, there were no associations. Conclusion: These data suggest that cemented fixation should be the preferred technique for most patients with displaced femoral neck fractures treated with hemiarthroplasty. The fact that stem fixation method did not affect revision rates for those patients with displaced femoral neck fractures treated with THA may be due to current practice patterns in the United States. Level of Evidence: Level III, therapeutic study.